Poorer Intermittent Sprints Performance in Ramadan-Fasted Muslim Footballers despite Controlling for Pre-Exercise Dietary Intake, Sleep and Training Load - Aziz, Abdul Rashid; Che Muhamad, Ahmad Munir; Roslan, Siti Raifana; Ghulam Mohamed, Nazirah; Singh, Rabindarjeet; Yong, Michael Hwa Chia (MDPI, 2017)
This study examines the effects of Ramadan fasting on sprint performance during prolonged intermittent exercise in trained Muslim footballers, under controlled pre-exercise conditions. A within-group, cross-over study design with two non-fasted or Control trials performed before (i.e., CON1) and after (CON2) the Ramadan month, and with the Ramadan-fasted (RAM) trials performed within the Ramadan month. After familiarization, 14 players completed a modified 60-min (4 15-min exercise blocks interspersed with 3-min intervals) of the Loughborough Intermittent Shuttle Test (mLIST) of fixed speeds of walking, jogging, running, but with all-out effort sprints. During the interval periods, capillary blood glucose and blood lactate measures were taken, rectal and skin temperatures were recorded and maximal voluntary isometric contractions (MVIC) of the dominant leg and hand-grip were performed to provide some indication to the cause(s) of ‘fatigue’ during exercise. Players were provided with standardized 24-h pre-packed meals prior to all trials. Sleep hours were objectively assessed and perceived training loads were monitored and these were equivalent between RAM and CON trials. Sprint times throughout mLIST were significantly faster in both CON1 and CON2 as compared to RAM trials (all P < 0.017; d = small to moderate), and this poorer performance in RAM was observed as early as during the first 15-min of the mLIST. Blood markers, MVIC and thermoregulatory results were not substantially different between both CON and RAM trials. In conclusion, despite similarities in dietary intake, sleeping hours and training loads between conditions, results still indicate that Ramadan fasting had an adverse effect on prolonged intermittent performance. Nocebo effects plays a dominant role during exercise in the Ramadan-fasted state.